Laparoscopic totally extraperitoneal inguinal hernia repair with and without urethral catheterization a prospective randomized study in Hospital Raja Permaisuri Bainun, Ipoh - Kok Kwong, Jamie Chin (2013)

(untitled)
Background Urethral catheterization during laparoscopic inguinal hernia repair remains a common surgical practice in spite of the insufficient evidence supporting its routine use. The aim of this study was to prospectively evaluate the utility of urethral catheterization during laparoscopic totally extraperitoneal inguinal hernia repair (TEP). Methods Patients undergoing elective laparoscopic totally extraperitoneal inguinal hernia repair were randomized into two groups: catheter and non-catheter groups. The main outcome of the study was to assess the feasibility and safety of performing elective laparoscopic hernia repair (TEP) without urethral catheterization. Results A total of 162 patients consented to randomization and 148 patients underwent surgery. The other 14 patients defaulted surgery. The catheter group had 72 patients while the non-catheter group had 76 patients (p = 0.818). Patient characteristics and operative parameters were comparable in both groups. There were no major operative complications in both groups and only 3 patients required conversion to open hernia repair. Two patients required postoperative catheterization, 1 patient from each group (p = 0.738). No patients from the non-catheter group required intraoperativecatheterization. A total of 19 patients (12.8%) from the catheter group had urinary symptoms compared to 7 patients (4.7%) in the non-catheter group and the difference was statistically significant (p = 0.006). However, there were no patients who had bacteriuria or urinary tract infection. Conclusion Laparoscopic totally extraperitoneal inguinal hernia repair without the routine use of urethral catheter does not compromise the safety or ease of the surgery. Keywords: Laparoscopic totally extraperitoneal inguinal hernia repair, TEP, urethral catheterization